The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pone.0238606
|View full text |Cite
|
Sign up to set email alerts
|

Martian biolith: A bioinspired regolith composite for closed-loop extraterrestrial manufacturing

Abstract: Given plans to revisit the lunar surface by the late 2020s and to take a crewed mission to Mars by the late 2030s, critical technologies must mature. In missions of extended duration, in situ resource utilization is necessary to both maximize scientific returns and minimize costs. While this present a significantly more complex challenge in the resource-starved environment of Mars, it is similar to the increasing need to develop resource-efficient and zero-waste ecosystems on Earth. Here, we make use of recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Another example of an enhanced, melanin-based radiation protection agent that is potentially bio-based is selenomelanin: it was found that under increased radiation, nanoparticles of the compound could efficiently protect cells against cell cycle changes 59 . In future, blends or layers of melanin with other materials, analogous to the concept of Martian ‘biolith’ 60 , may yield composites that more efficiently shield against cosmic rays. Advanced additive manufacturing technologies such as 3D bioprinting, may ultimately also allow the creation of smart ‘living composite’ materials that are adaptive, self-healing and largely autonomous 61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of an enhanced, melanin-based radiation protection agent that is potentially bio-based is selenomelanin: it was found that under increased radiation, nanoparticles of the compound could efficiently protect cells against cell cycle changes 59 . In future, blends or layers of melanin with other materials, analogous to the concept of Martian ‘biolith’ 60 , may yield composites that more efficiently shield against cosmic rays. Advanced additive manufacturing technologies such as 3D bioprinting, may ultimately also allow the creation of smart ‘living composite’ materials that are adaptive, self-healing and largely autonomous 61 .…”
Section: Resultsmentioning
confidence: 99%
“…As a biological compound, natural melanin may be readily available through ISRU by means of biotechnology. In future, blends or layers of bio-derived melanin with other materials, analogous to the concept of Martian ‘biolith’ [61], may yield composites that more efficiently shield against radiation. This also opens the opportunity for melanin to be used as a constituent in fibrous composites for radiation shielding [62], to be used in textiles, such as EVA-suites or inflatable spacecraft and habitats.…”
Section: Resultsmentioning
confidence: 99%
“…As a biological compound, natural melanin may be readily available through ISRU and producible by means of biotechnology (Martínez et al, 2019 ). To increase density, as well as for structural purposes, fungal biomass or melanin itself could be integrated with in situ resources that are abundant at the destination, such as regolith (Simonsen et al, 1991 ), analogous to the concept of Martian “biolith” (Shiwei et al, 2020 ). In a different application, layers of melanin could be applied to components, such as EVA-suites or inflatable spacecraft and infrastructure, as a constituent of fibrous composites (Blachowicz and Ehrmann, 2021 ), e.g., in textiles or as resin, to protect them from the surface damage caused by ultraviolet light.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, chitin and its sub-products have been massively studied, aiming at the development of a composite with low manufacturing requirements, ecological integration, and versatile utility for Mars colonization. These studies have demonstrated the high potential of chitin application in a wide range of industries, which demonstrates the high importance and possibilities for uncommon applications of this material . Also, this polysaccharide is an essential compound for the survival of various pests in world crops, because its degradation represents an important and specific target to reduce losses in the field and improve plantation yield .…”
Section: Chitinases As Biopesticides Against Fungi Insects and Viruse...mentioning
confidence: 91%
“…These studies have demonstrated the high potential of chitin application in a wide range of industries, which demonstrates the high importance and possibilities for uncommon applications of this material. 12 Also, this polysaccharide is an essential compound for the survival of various pests in world crops, because its degradation represents an important and specific target to reduce losses in the field and improve plantation yield. 13 It is a structural component of the fungal cell wall but also in the eggshell of nematodes and the cutaneous and peritrophic matrix of insects (thin acellular sheath that lines the intestinal epithelium of most insects).…”
Section: ■ Introductionmentioning
confidence: 99%